When to say “I love you”: Before or after sex? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
There are no hard and fast rules on when one should say 'I love you', or who should say it first. Yet, the implications either way can be profound. Taking an evolutionary-economics perspective, these words, for men, could be taken as "bids for sexual access". Women, on the other hand, might view it differently, depending on whether the words were uttered before or after sex. SMU associate professor Norman Li examines what it is that romantic partners really mean when they say "love".